Localization of Left Ventricular Lead Electrodes in Relation to Myocardial Scar in Patients Undergoing Cardiac Resynchronization Therapy. Issue 21 (6th November 2018) - Bisson, Arnaud; Pucheux, Julien; Andre, Clémentine; Bernard, Anne; Pierre, Bertrand; Babuty, Dominique; Fauchier, Laurent; Clementy, Nicolas
Abstract : Background: The efficacy of cardiac resynchronization therapy may be reduced in the event of pacing within myocardial fibrosis. We aimed to develop a method to determine the anatomical relationships between the left ventricular (LV) lead and myocardial fibrosis. Methods and Results: In consecutive patients indicated for cardiac resynchronization therapy, cardiovascular magnetic resonance imaging with late gadolinium enhancement assessment was performed before implantation. After implantation, an injected computed tomography scanner (CT scan) was performed. The 2 imaging techniques were fused to assess the LV lead position relative to myocardial scar. A total of 68 patients were included. Myocardial scar was found in 29 (43%) and was localized in lateral segments in 14 (21%). Scar was significantly associated with male sex, ischemic cardiomyopathy, a Selvester score adapted to left bundle branch block (LBBB Selvester), and Selvester criteria for localizing lateral fibrosis (V2 S/S′ ratio). Image fusion was feasible in all patients. Position within myocardial scar was confirmed for 6 electrodes in 3 patients. Prolonged QRS duration during LV pacing ≥139% predicted electrode positioning within scar tissue (sensitivity, 83%; specificity, 91%; P =0.002). Conclusions: In cardiac resynchronization therapy patients, fusion between preimplantation cardiovascular magnetic resonance and a postimplantation injected computed tomography scan is a feasible technique. Prolongation of the QRS duration during LV pacing predicts pacing within myocardial scar. Accurate location of LV lead pacing electrodes on the epicardial surface relative to myocardial scar, either by imaging or ECG analyses, may help improve cardiac resynchronization therapy response in selected patients.